STRENGTH OF AGED WOOD IN OLD CONSTRUCTIONS - Fedyukov, Vladimir; Chernov, Vasilii; Chernova, Maria (Journal of Applied Engineering Science, 2020)
The results of comprehensive research into spruce and pine wood in a structure after 70 years of its exploitation are presented. Significant changes in the wood in terms of compressive strength along the grain and static bending across the grain were revealed compared with fresh wood. The magnitude of these changes depends on the location of wood in the walls of the structure relative to the cardinal points.